Pengaruh Pengalaman Kerja, Independensi,Objektivitas,Integritas,Kompetensi Dan Etika Terhadap Kualitas Audit - Shella Febrianisa; Cris Kuntadi (Akuntansi, 2024)
The quality of the audit produced by the auditor is an important factor in ensuring the integrity and reliability of an entity's financial reports. This research aims to examine the influence of work experience, independence, objectivity, integrity, competence and ethics on audit quality. Auditors' work experience can improve their ability to detect errors and make appropriate assessments. The auditor's independence, objectivity and integrity guarantee that the audit process is carried out professionally and is not influenced by certain interests. In addition, auditor competency and ethics are important factors in ensuring that audits are carried out with capability and high ethical standards. This research uses primary data collected through questionnaires distributed to auditors who work at Public Accounting Firms (KAP) in Indonesia. The work experience variable is measured by the number of years working as an auditor, independence is measured by relationships with clients, objectivity is measured by the ability not to be influenced by pressure, integrity is measured by the principles of professional ethics, competence is measured by audit knowledge and abilities, and ethics is measured by the application of a professional code of ethics. Audit quality is assessed based on the auditor's perception of the quality of the audit produced. The research results show that work experience, independence, objectivity, integrity, competence and ethics have a positive and significant influence on audit quality. These findings indicate that the higher the auditor's work experience, independence, objectivity, integrity, competence and ethics, the better the resulting audit quality. This research provides important implications for the audit profession in improving audit quality through improving the factors that influence it. The results of this research can also be used as consideration for regulators and other stakeholders in establishing standards and guidelines for the audit profession.